2020
DOI: 10.31703/gsr.2020(v-iv).04
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship of Job Stress and Turnover Intentions by taking Work-Family Conflict and Family Work Conflict as Mediators

Abstract: Turnover intentions are to lose skilled workers. Job stress is the cause of the use of employee turnover. Work-Family Conflict (WFC) and Family Work Conflict (FWC) were considered to be intermediaries between the employees' Turnover Intentions. This study investigates the relationship between Job Stress and Turnover Intentions. It was studied by taking Work-Family Conflict (WFC) and Family Work Conflict (FWC) as mediator. Research is based on a quantitative approach. Data were collected from employees in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…Finally, work-family conflicts have been found to mediate job-related conditions and outcomes, which was confirmed by our study. The mediating role in the positive relationship between job stress and turnover intentions was confirmed in accordance with Khan and Muhyuldeen's (2020) study, however, the mediating role of work-family conflict in the relationship between fear of COVID-19 and turnover intention, was to the best of our knowledge new in the research field.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, work-family conflicts have been found to mediate job-related conditions and outcomes, which was confirmed by our study. The mediating role in the positive relationship between job stress and turnover intentions was confirmed in accordance with Khan and Muhyuldeen's (2020) study, however, the mediating role of work-family conflict in the relationship between fear of COVID-19 and turnover intention, was to the best of our knowledge new in the research field.…”
Section: Discussionsupporting
confidence: 83%
“…Mediating role of work-family conflict. The relationship between COVID-19 phobia and turnover intentions, as well as job stress and turnover intentions, is more than a simple effect (Khan and Muhyuldeen, 2020). As stated in hypothesis 1, fear of COVID-19 is positively associated with work-family conflict and hypothesis 3 states that work-family conflict is positively associated with women's turnover intention.…”
Section: 36mentioning
confidence: 90%
“…When assessing mediating hypotheses, the findings showed a higher level of significance in the mediating relationship, and based on the findings, the proposed hypotheses were accepted based on t and p values. The significant findings of the current study are also consistent with the literature, as Khan and Muhyuldeen (2020) discovered that WFC plays a significant mediating role between job stress and TI. According to current research, there is a high level of work stress, as well as a high rate of conflict.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these statistical calculations, it can be concluded that the H5 hypothesis, which states the positive and significant influence of Work Stress on Turnover Intention, is supported by the findings of this study. The results of this study were reinforced byKhan (2020) in his research investigating the relationship between Work Stress and Turnover Intentions. Examined by taking Work-Family Conflict and Family Work Conflict as mediators.…”
supporting
confidence: 55%
“…In line with these results, Kremer (2016) also found that work-school conflict positively affects work stress and tension. Khan (2020), in his research, investigated the relationship between Work Stress and Turnover Intention. Examined by taking Work-Family Conflict (WFC) and Family-Work Conflict (FWC) as mediators.…”
Section: Work-school Conflict and Work Stressmentioning
confidence: 99%